Effects of dietary amylose/amylopectin ratio on antioxidant ability and amino metabolism in the liver of weaned piglets undergoing feed transition and challenged with lipopolysaccharide - Yang, Can; Tang, Xiaowu; Wang, Min; Yang, Han; Yang, Huansheng; Wang, Yancan; Yin, Yulong (Frontiers in Nutrition, 2025)
To find out whether dietary amylose/ amylopectin ratio (DAR) could attenuate injury in lipopolysaccharide (LPS)-challenged piglets, sixty male weaned piglets (Duroc × Landrace × Yorkshire, 21 days old, 6.51 ± 0.64 kg) were allotted to 5 dietary treatments with 12 cages per treatment, and fed ad libitum with diets different in DAR (0.00, 0.20, 0.40, 0.60 and 0.80). Feed transformation occurred from D15 to D21. On day 28, 12 h before slaughter, pigs were intraperitoneal injected with 100 μg/kg body weight LPS or sterile saline. Results showed that LPS stress caused an increase in serum urea nitrogen (UREA) and triglyceride (TG), but a decrease in alanine aminotransferase (ALT) activity and glucose (GLU) concentration (p < 0.05). Serum immunoglobulin G (IgG) concentration increased in DAR 0.80 but decreased in other groups after LPS stress (p < 0.05). Compared with the control group, concentrations of Ile, Leu, Phe, Val, Thr, Arg decreased in serum but increased in liver after LPS stress (p < 0.05). Serum Arg, Tyr, Sar, Ans, Orn increased linearly with increasing DAR (p < 0.05). Piglets in diet DAR 0.00 had highest superoxide dismutase (SOD1) and glutathione peroxidase 1 (GPX1) mRNA expression in liver than those in other groups (p < 0.05). There was significant effect of LPS stress * dietary DAR on total SOD activity and SOD1 mRNA gene expression (p < 0.05), LPS stress caused an increase in those two indices for pigs in groups 0.00 and 0.80. Piglets in diet 0.80 had the highest hepatic Cu, Fe, Mn, Zn concentrations than those in other groups (p < 0.05). Cecal indol(e) concentration was higher in diet 0.00 than that in diet 0.80 (p < 0.05). After LPS stress, colonic skatole concentration increased in DAR 0.40, 0.80 but decreased in other groups (p < 0.05). In conclusion, adverse effects of the LPS challenge could be reversed by feeding weaned piglets with low or high DAR diet through regulating amino metabolism and antioxidant function.